Role of cholangitis in predicting survival in patients with carcinoma of the ampulla of vater. (December 2020) - D'Silva, Mizelle; Han, Ho-Seong; Yoon, Yoo-Seok
Abstract: Background: There have been strong suggestions that acute inflammation promotes tumour growth, and has a tendency for increased invasiveness, leading to poor survival after surgery. When cholangitis coexists with ampulla of vater cancer, the patient's prognosis may be influenced by the acute inflammatory status of the bile duct. We evaluated the relationship between the severity of acute cholangitis, preoperative CRP levels and survival. Methods: We retrospectively analysed 154 patients who underwent surgical resection for AOV cancer between January 2003 and November 2018. Cholangitis was graded according to Tokyo Guidelines 2018. Patients were categorised into two groups based on their CRP levels: CRP > 1 mg/L and CRP ≤ 1 mg/L. Relationship of cholangitis grade and CRP >1 mg/L with survival was assessed. Results: The mean age of the patients was 65.8 years. Preoperative cholangitis was present in 40 (25.9%) patients, of which 28 (18.2%) had mild cholangitis, 11 (7.1%) had moderate cholangitis, and one (0.6%) had severe cholangitis. CRP was elevated preoperatively in 56 (36.4%) patients. The median follow-up period was 33.5 months. Severity of cholangitis significantly affected the overall survival (P < 0.001) and disease-free survival (P < 0.001). Patients with mild cholangitis had a median overall survival of 43 months compared to 14 months in those with moderate cholangitis. A preoperative CRP level of >1 mg/L was significantly associated with poor overall survival (P = 0.023) but not with disease-free survival (P = 0.128), although it was associated with a trend towards poorer survival. The survival rate of patients with CRP ≤1 mg/L was 77.4%, whereas that of patients with CRP >1 mg/L was 56.7%. In multivariable analysis, age >65 years (P = 0.015), cholangitis grade (P = 0.050), CRP > 1 mg/L (P = 0.045), venous invasion (P = 0.005), and perineural invasion (P = 0.034) were independent prognostic factors for overall survival while cholangitis grade (P = 0.049) and perineural invasion (P = 0.004) were independent prognostic factors for disease-free survival. Conclusion: Acute inflammation when associated with cancer can have a negative effect on patient's survival. Patients with higher grades of cholangitis should be adequately treated to improve the inflammatory status. Highlights: Acute inflammation promotes tumour growth and has a tendency for increased invasiveness. Acute inflammation associated with cancer can have a negative effect on patient's survival. Patients with higher grades of cholangitis should be adequately treated to improve survival.